2023
DOI: 10.15619/nzjp/48.3.03
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of telerehabilitation in response to COVID-19: Lessons learnt from neurorehabilitation clinical practice and education

Abstract: The health response to the COVID-19 pandemic has had significant impacts on neurorehabilitation provision both internationally and in New Zealand. Telerehabilitation, the delivery of rehabilitation at a distance using information and communication technologies, was advocated as a means of addressing the rehabilitation needs of our patients while maintaining physical distancing and reducing the risk of viral transmission. Despite research evidence indicating that telerehabilitation is as effective as in-person … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(83 citation statements)
references
References 28 publications
6
76
0
1
Order By: Relevance
“…These subthemes under the PT factor theme were supported by the experiences that Signal et al (2020) reported from a neurorehabilitation environment. In their experiential research, the key component were related to setup, assessment, and treatment considerations.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…These subthemes under the PT factor theme were supported by the experiences that Signal et al (2020) reported from a neurorehabilitation environment. In their experiential research, the key component were related to setup, assessment, and treatment considerations.…”
Section: Discussionmentioning
confidence: 66%
“…Considerations were given around the ability to engage in interdisciplinary care at the team as well as family levels. Although this study involved perceptions related to the adult concussion population, Signal et al (2020) reported similar aligning perspectives towards a team-oriented, family-centred approach when applying VPT to the paediatric concussion population. Concepts of trust and knowledge-sharing in an interdisciplinary setting may be associated with improved provider SE (Chang et al, 2015), as well as team self-reflection (Signal et al, 2020) when providing VPT.…”
Section: Results For Research Questionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, it is vital to observe that prescribing exercises to patients is a multifaceted process and demands advanced therapeutic knowledge to advance its effectiveness and adherence, including communication and education. As such, the implementation of TR to occupational therapy should be conducted based on a paradigm change to realize an effective patient-based TR [19].…”
Section: Discussionmentioning
confidence: 99%